Prudent Budgetary Policy: Political Economy of Precautionary Taxation. - van der Ploeg, F (CESifo Group Munich, 2007)
The theory of tax smoothing and determination of public debt with uncertain future national income is extended for prudence. A prudent government deliberately underestimates future national income and the tax base, especially if the variance and persistence of shocks hitting the tax base are large and the tax rate and the unemployment benefit are large. As a precaution the tax rate is set higher and the level of public spending lower. As a result, as income and the tax base turn out to be bigger than budgeted, the minister of finance enjoys windfall revenues and is able to gradually reduce debt and debt service over time. This permits, depending on political preferences, either gradual cuts in the tax rate, gradual increases in government spending or a combination of both. It is easy to allow for government assets as well. Finally, political economy justifications are offered of why it is desirable to appoint a strong and pessimistic minister of finance. In particular, we show that prudence is able to offset the intertemporal spending, tax and debt biases resulting from the common-pool distortions. If the minister of finance and the prime minister are given as many voting rights as the spending ministers combined, the intratemporal common-pool distortions of an excessively large public sector are eliminated as well. A strong and pessimistic minister of finance can thus control the impatient profligacy of squabbling spending ministers. However, if voters care about outcomes on election eve, prudence may be abused for short-run electoral gains. Opportunistic manipulation of election results, however, also dampens the intertemporal common-pool distortions.